Bastille Day Dinners in Scotland and Festivals in France: Transnational Relations or Monologues in the 1790s? - Rémy DUTHILLE (E-REA)
In the 1790s, Scotsmen were involved in celebrations of the French Revolution in both Scotland and France. How far did those men, stemming mainly from the elites, manage to relate with the French? The article examines Bastille Day dinners given in Scotland from 1790 to 1792, international festivals organized by the French Jacobins in harbour cities from 1790 to 1792, as well as Thomas Muir’s welcome reception held in Bordeaux in 1797. Though the celebrations look very dissimilar, in each case the question of the foreigner was raised; the guests pledged friendship and peace to the foreigners, but tended to idealize those foreigners as incarnations of nations or revolutionary principles, rather than engage at a personal, concrete level with them.